Efficacy of pamidronate in children with chronic non-bacterial osteitis using whole body MRI as a marker of disease activity - C. S. Bhat; M. Roderick; E. S. Sen; A. Finn; A. V. Ramanan (BMC, 2019)
Abstract Background To study the response to pamidronate using whole body magnetic resonance imaging (WB-MRI) in children with chronic non-bacterial osteitis (CNO) in a tertiary health centre. Methods The medical records of children under the age of sixteen with a diagnosis of chronic non-bacterial osteitis between 2005 and 2018 were reviewed. All those who were treated with pamidronate were included and relevant data was collected. Response to therapy was determined based on the status of lesions on WB- MRI. Results Forty six patients were included in the study. Pre- and post-treatment WB-MRI was available in forty patients. Cumulative lesions pre-treatment were 150 and reduced to 45 (30%) post-treatment. Seventeen patients (42.5%) had a good response with complete resolution of all lesions and nine patients (22.5%) worsened during or following treatment with pamidronate. Vertebral disease had a good response and 82.3% of the lesions resolved completely. Conclusion Our study describes the experience with pamidronate in a tertiary health centre using WB-MRI as a marker of disease activity. Pamidronate was well tolerated in our cohort and treatment response was fairly good. Significance and innovation 1. Bisphosphonates can be used in the treatment of CNO when response to NSAIDs is suboptimal. 2. In the presence of spinal or mandibular lesions bisphosphonates were used as first line. 3. Treatment was escalated to a TNF blocker when response to bisphosphonates was suboptimal.